Development of Interactive Learning Media Based on Smart APP Creator on The Material of Building Self-Identity In Diversity to Improve the Learning Outcomes of Fourth Grade Elementary School Students - Nuraida; Setiawan, Deny; Yusnadi (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This study aims to develop interactive learning media based on smart apps creator on the material of building identity in diversity to improve the learning outcomes of grade IV elementary school students. The research method uses Research and Development (RnD) with the 4D model (Define, Design, Develop, and Disseminate). This research was conducted at SDN 057224 Paluh Gusta with the subjects of grade IV elementary school students as many as 25 students. Data were collected through a validation questionnaire of material, media, and language experts to assess feasibility, then a practicality questionnaire assessed by teachers and tests that intend to expose student learning outcomes. The results showed the level of feasibility by material experts 90%, media experts 92%, and linguists 91%, with a classification of "Very Good". Practicality reached 93% with a classification of "Very Practical". Then, student learning outcomes increased significantly from pretest 65 to posttest 90 with the n-gain test reaching 0.714 with a classification of "Very High". So it is concluded that the interactive learning media based on smart apps creator on the material of building identity in diversity developed is feasible and valid and able to improve student learning outcomes.